2011
DOI: 10.19030/jber.v4i1.2628
|View full text |Cite
|
Sign up to set email alerts
|

Family Owned Business Fraud: The Silent Thief

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">The ACFE 2002 Report to the Nation on Occupational Fraud and Abuse shows &ldquo;The per-employee losses from fraud in the smallest businesses are 100 times the amount of their largest counterparts.&rdquo; Further, major factors contributing to small business fraud include: inadequate employee prescreening; limited controls and too much tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The two factors that are regarded as contributing most to family business success are the trust between family members, their healthy relationship with employees (Flottum, 2011; Sawyers, 2010) and their passion for their business (Reynolds, 2012). Too much trust in family firms could reduce controls that prevent fraud detection (Bledsoe and Wessels, 2006). Family values are often maintained by sustaining the success of a family firm (Parada et al, 2010).…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…The two factors that are regarded as contributing most to family business success are the trust between family members, their healthy relationship with employees (Flottum, 2011; Sawyers, 2010) and their passion for their business (Reynolds, 2012). Too much trust in family firms could reduce controls that prevent fraud detection (Bledsoe and Wessels, 2006). Family values are often maintained by sustaining the success of a family firm (Parada et al, 2010).…”
Section: Trustmentioning
confidence: 99%
“…A United States National Family Business Panel of 311 small-family firms indicated that male-owned small-family businesses that were exposed to natural disaster without federal disaster assistance showed significant resiliencethis was not the case with female-owned family businesses (Danes, Lee, Amarapurkar, Stafford, Haynes and Brewton, 2009). On the other hand, resilience of small-family firms can be threatened by a lack of internal controls and too much trust in employees (Bledsoe and Wessels, 2006).…”
mentioning
confidence: 99%